Implementation IMPLEMENTATION OF RENOVATION ASSISTANCE FOR THE CONSTRUCTION OF THORIQUL KARIM MOSQUE TOLOK TEGAL GEDE KARANGANYAR: Thoriqul Karim Mosque of Renovation - Ichwan Prastowo (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2023)
The urgent need as a means of worship activities for community worshippers in RW 10 and the very many surrounding residents, encouraged the management of the Thoriqul Karim Tolok Tegalgede Karanganyar Mosque to carry out renovations to be able to accommodate all worshippers. Limited land and the size of the building demand for the construction of the mosque to be the 2nd floor. In this community service activity, it is carried out starting from the stages of preparation, implementation and the end of implementation. The purpose of this activity is to help the community in the process of building a mosque so that it becomes a safe and comfortable means of worship. The activities carried out are participating in planning, implementation and supervision during construction. The result of the activities that have been carried out today is the realization of the mosque in accordance with the expectations of the community.